تقويم جودة خدمات الرعاية الصحية المقدمة في مستشفى بنغازي لطب و جراحة الأطفال من وجهة نظر مرافقي متلقي الخدمة - عائشة عمران النجار (Scientific Journal of University of Benghazi, 2019)
Hospitals are an important part of the infrastructure in all countries of the world because of the essential role they play in providing health care services to all segments of society. The aim of this study is to evaluate and investigate the level of health care services provided by Benghazi Hospital for Pediatric Surgery from the point of view of the recipients of the service by answering the following questions: 1 - What is the level of quality of health care services in Benghazi children's hospital from the point of contact of the recipients of the service? 2- Are there differences between respondents' opinions regarding the quality of health services provided in Benghazi Children's Hospital due to the demographic variables (gender, age, academic qualification, place of residence)? In order to evaluate the quality of health care services, the study measures variables related to reception procedures, treatment of medical and nursing staffs, work procedures, health awareness, and the internal and external environment conditions of the hospital. The data was collected by using the analytical descriptive method .The study was applied to a sample of 100 of the recipients of the service through the measuring instrument (questionnaire). The findings of this study were: There were statistically significant differences in the responses of the respondents about the services provided due to the variable of academic qualification. There were no statistically significant differences due to other demographic variable (gender, age, place of residence) . Generally speaking the quality of health care services provided by children’s hospital in Benghazi was to certain extent of good quality. The main recommendations of this study are to confirm and disseminate the concept of quality of health services and to set the standards of application of the service to measure the performance and efficiency of the health team. In addition, there is a need to conduct studies and future research similar to the current study to promote the concept of quality in health services.